Integrating lymphovascular and perineural invasion into TNM staging: a novel ITNM system for enhanced prognostic stratification in colorectal cancer - Hu, Jiaqi; Zhang, Minghao; Qi, Yang; Wang, Yun; Xu, Dalin; Zhu, Kejin; Bu, Jun (Frontiers in Oncology, 2026)
BackgroundThe standard TNM staging system for colorectal cancer (CRC) fails to reflect true tumor biology because it ignores key histopathologic features such as lymphovascular and perineural invasion. We therefore developed and validated an “ITNM” classification that folds these two factors into the N stage, yielding more accurate prognoses and greater clinical value.MethodsA retrospective cohort of 442 stage I–III CRC patients underwent radical resection (2015–2021). Propensity score matching (PSM) created balanced exposure (LVI/PNI-positive, n = 185) and control (LVI/PNI-negative, n = 257) groups. The ITNM system was constructed by upstaging the N category based on LVI/PNI status. Predictive performance was evaluated using C-index, ROC-AUC, calibration curves, decision curve analysis (DCA), net reclassification improvement (NRI), and integrated discrimination improvement (IDI).ResultsMultivariate analysis confirmed LVI (HR = 2.10, p = 0.018) and PNI (HR = 2.28, p = 0.025) as independent predictors of overall survival (OS). The LVI/PNI-positive group had significantly lower 5-year OS (69.5% vs. 88.2%, p < 0.001). The ITNM system demonstrated superior discriminative ability for 5-year OS (C-index = 0.715; AUC = 0.735, 95% CI: 0.691–0.776), excellent calibration (p = 0.489), and higher net benefit on DCA. Significant reclassification improvement was confirmed (NRI = 0.306, p < 0.001; IDI = 0.061, p < 0.001).ConclusionThe ITNM system significantly enhances prognostic accuracy by integrating LVI and PNI into TNM staging, enabling risk-adapted therapeutic decision-making and representing a paradigm shift in CRC stratification.